2017
DOI: 10.9775/kvfd.2016.16901
|View full text |Cite
|
Sign up to set email alerts
|

Karasinekteki (Musca domestica) Antimikrobiyal Peptidler Salmonella pullorum ile Enfekte Tavuklarda Bağırsak Lactobacillus acidophilus ve Mukozal Epitel Hücrelerini Etkiler

Abstract: Pullorum disease, which is one the most serious intestinal diseases in poultry production, is generally treated by adding antibiotics to the feed of infected chickens. Although antibiotics are generally quite effective against the disease, they can harm small intestinal flora and mucosa. The objective of this experiment was to determine if antimicrobial peptides (AMPs) from housefly (Musca domestica) larvae can be used to treat pullorum disease. The study included AMPs extracted from Salmonella enteric serovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…For instance, HF larvae and pupae express AMP's such as defensin in several tissues, which act upon invading Gram-positive bacteria (Andoh et al, 2018;Dang et al, 2010). Experiments with HF AMPs even showed that the administration to Salmonella pullorum infected chickens can serve as effective treatment of the intestinal disease, without having negative effects on mucosal epithelial cells (Wang et al, 2017). The novel defensin-like peptide 4 (DLP4) detected in BSF larvae exhibits activity against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus (Park et al, 2015).…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…For instance, HF larvae and pupae express AMP's such as defensin in several tissues, which act upon invading Gram-positive bacteria (Andoh et al, 2018;Dang et al, 2010). Experiments with HF AMPs even showed that the administration to Salmonella pullorum infected chickens can serve as effective treatment of the intestinal disease, without having negative effects on mucosal epithelial cells (Wang et al, 2017). The novel defensin-like peptide 4 (DLP4) detected in BSF larvae exhibits activity against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus (Park et al, 2015).…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…In some cases, the production of these compounds must be stimulated. For example, in a previous study, housefly larvae were inoculated with a suspension of Salmonella pullorum cells to obtain AMP ( 19 ). Another example is a study where crickets were infected with Photorhabdus asymbiotica and derived from the infection, and glidobactin A, luminmycin, and luminmycin D were isolated ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial activity was determined by using the disk diffusion test. The methodology carried out was the one proposed by Wang et al ( 19 ) with slight modifications. First, the strains E. coli ATCC 25922, S. aureus ATCC 25923, E. aerogenes ATCC 13048 Salmonella sp., and P. aeruginosa ATCC 77853 were inoculated in Luria broth and incubated for 48 h at 35 ° C. Once there was growth (presence of turbidity), the test was performed using Luria agar; paper disks were soaked in the samples for 30 s, then placed on an agar plate, and incubated for 48 h at 35 ° C. As a control, amikacin 1:10 v/v was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations